Warunki mikroklimatyczne we wnętrzu boru sosnowego na Mierzei Łebskiej - Kolendowicz, Leszek; Bednorz, Ewa (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2010)
The observed regularities concerning the differentiation of the temperature of individual layers of the pine forest point to the assumption by the tree crowns of the role of the active surface, which is served by the soil surface in the area devoid of vegetation. This is supported among others by the higher values of air temperature to a height of 6 m above ground level between 12.00–15.00 hours, this means during the maximum of the intensity of solar radiation (Molga 1970). Moreover the lowest values of air temperature appears to a bottom part of the pine forest above ground level between 15.00–8.00 hours. The inversion of temperature near the ground is a natural phenomenon in the night hours, particularly at dawn. If no compact vegetation layer is present, it comes into being during calm nights and in the predawn hours above the active surface (above the ground) due to the radiation of heat from the ground zone to higher layers of the atmosphere. Appearance of the cool layer in the bottom part of pine forest under the hight of 6–8 m above ground level during the points to the assumption of the role of the active surface by pine crowns at this very height (Molga 1970; Paszyński et al. 1999). Differences in temperature between the open area and the forest interior or the layer of air above the forest point to the differentiation of energy exchange processes, this being dependent on the nature of the active surface. The forest area is characterised by a clearly lower albedo value than the area of the grey sand dune upon which the MAWS 201 station is located. In addition, forest areas may accumulate a greater amount of heat during the day than the sandy soil covered with grassy vegetation. The stored heat, the quantity of which depends both on the heat capacity and the albedo value, is transferred to the atmosphere in the night. Thus, the layer of atmosphere above the forest is usually warmer at night than the air located above the ground not covered with dense and tall vegetation. During the day, the soil is considerably warmer than the active surface of the forest, which results from the lower heat capacity of the soil. For this reason, a considerably greater quantity of energy radiates in a longwave form than in the case of the forest, and thus the temperature of air above the ground during the day is higher (Paszyński et al. 1999). During the day, the interior of the forest is in turn cooler than the areas devoid of vegetation due to considerably weaker solar radiation reaching the forest bed. At night, however, due the emission of additional quantities of heat from the tall vegetation and the more difficult emission of energy from the forest soil to the atmosphere above the forest (due to its absorption by the vegetation), the temperature of air inside the forest is usually higher than in the area devoid of vegetation (Geiger 1942; Molga 1970). The distribution of humidity in individual layers of the researched forest community does not differ considerably from the results of research carried out on this topic by other authors. The greater content of water vapour in the air inside the forest in comparison with the open area results directly from the considerable intensity of evaporation of the lower active surface of the forest. The maintenance of the greatest air humidity in the lower zone of pine crowns is most probably connected with their additional transpiration (apart from the transpiration of vegetation of the forest bed) and low wind velocities, which make it possible for water vapour to gather and remain in this zone (Molga 1970).
Keywords: Słowiński National Park,e; Pine forest; Microclimate